The Impact of Corticosteroids on Mortality in Acute Exacerbations of Idiopathic Pulmonary Fibrosis: A Meta-Analysis - Pier-Valerio Mari; Angelo Coppola; Lorenzo Carriera; Francesco Macagno (Advances in Respiratory Medicine)
Background: Acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) is one of the most challenging events in the disease course due to the high mortality despite treatment. The role of corticosteroid treatment in AE-IPF has never been defined, even though it is used in current clinical practice. We performed a meta-analysis to determine the effects of steroid treatment on the acute exacerbation outcomes in idiopathic pulmonary fibrosis (IPF). Objectives: To evaluate the impact of steroids on mortality in patients affected by an acute exacerbation of IPF. Methods: This meta-analysis was performed in accordance with the PRISMA statement. A systemic literature search was conducted through Google Scholar, Scopus, WoS, PubMed, and JSTOR. Manuscripts from January 2014 to September 2024 were included in the analysis. Articles were included on whether participants had an acute exacerbation of IPF. Regarding the intervention performed, we evaluated the studies in which patients underwent treatment with corticosteroids. As outcomes, studies were included if they analyzed the overall mortality. Results: A total of 2156 records were initially identified. Nineteen studies (3277 patients) were ultimately included in the final analysis, comparing 1552 patients who received steroids to 1725 patients without steroids. Steroid treatment poses a higher risk, as suggested by the summary measures (RR of 1.78; CI 1.29–2.76, p = 0.00001). Conclusions: This meta-analysis investigated the debated role of corticosteroid treatment during acute exacerbation of idiopathic pulmonary fibrosis. Overall, steroid therapy is associated with increased risk. Clinicians should carefully weigh the risks and benefits of corticosteroid therapy in acute exacerbation of IPF.